Coronavirus: Pandemics, artificial intelligence and personal data: How to manage pandemics using AI and what that means for personal data protection - CHIK, Warren B. (Institutional Knowledge at Singapore Management University, 2020)
This chapter discusses the hearing of essential and urgent court matters in the Singapore courts during the COVID-19 pandemic. On 27 march 2020, the Singapore judiciary notified courst users that remote hearings were to be implemented for certain types of hearings by means of video and telephone conferencing facilities. Court users were also provided with indicative lists of matters which might be considered essential and urgent.